A project co-created with the community to mitigate loneliness in midlife women - Nadia Corsini; Fiona Dorman; Jodie Scott; Amanda Wright; Deborah Turnbull; Carmel Williams; Carmel Williams; Deborah Bates; Bernadette Reading; Hayley Everuss; Fanke Peng; Rachael Pearse; et al. (Frontiers Media S.A., 2024)
This paper describes how a team of researchers, policy stakeholders and community members came together to co-create prevention-oriented and community-informed solutions to address loneliness in women-The Loneliness Project. Our aim is to encourage community partnerships and collective effort to address public health approaches to loneliness by developing a shared understanding of the issue from multiple perspectives and through the co-creation process, highlighting the key factors for co-creating a funding application for a community demonstration project.